2019
DOI: 10.1016/j.sjbs.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory activity of Tetragronula species from Indonesia

Abstract: Anti-inflammatory drugs inhibit inflammation, particularly those classified as nonsteroidal anti-inflammatory drugs (NSAIDs). Several studies have reported that propolis has both anti-ulcerogenic and anti-inflammatory effects. In this study, we investigated the bioactive compound and in vivo anti-inflammatory properties of both smooth and rough propolis from Tetragronula sp. To further identify anti-inflammatory markers in propolis, LC-MS/MS was used, and results were analyzed by Mass Lynx 4.1. Rough and smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
35
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 33 publications
2
35
0
3
Order By: Relevance
“…Our previous study has shown that Sulawesi propolis may perform an antifungal activity to Candida albicans, C. tropicalis, C. krusei, C. parapsilosis, C. glabrata, and Cryptococcus neoformans ( Pratami et al, 2020 , Sahlan et al, 2020 ). It also exhibits antioxidant and anti-inflammatory activity due to the high phenolic content ( Christina et al, 2018 , Pratami et al, 2018 , Sahlan et al, 2019 ). The pharmacological potency of Sulawesi propolis should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study has shown that Sulawesi propolis may perform an antifungal activity to Candida albicans, C. tropicalis, C. krusei, C. parapsilosis, C. glabrata, and Cryptococcus neoformans ( Pratami et al, 2020 , Sahlan et al, 2020 ). It also exhibits antioxidant and anti-inflammatory activity due to the high phenolic content ( Christina et al, 2018 , Pratami et al, 2018 , Sahlan et al, 2019 ). The pharmacological potency of Sulawesi propolis should be further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Propolis compounds are diverse according to the region ( Alday et al, 2016 ). Beforehand, Sulawesi propolis compounds from North Luwu have been identified by several research ( Mahadewi et al, 2018 , Miyata et al, 2019 , 2020a Miyata et al, 2020b , Sahlan et al, 2019 ). Sulawesi propolis previously was known to be produced by Tetragonula aff.…”
Section: Introductionmentioning
confidence: 99%
“…Sulawesi propolis exhibits antifungal activity to Candida albicans, C. tropicalis, C. krusei, C. parapsilosis, C. glabrata and Cryptococcus neoformans ( Sahlan et al, 2020 ). Other study showed that Sulawesi propolis is potential to be developed as a non-steroid anti-inflammatory drug and antioxidant agent ( Christina et al, 2018 , Sahlan et al, 2019 ). These facts encourage us to do more investigations regarding the health benefits of Sulawesi propolis.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation is an immune response against the invasion of foreign objects, tissue damage, or both (1,2). The causes of inflammation include mechanical trauma, microorganism, physical effects, and chemical substances (3). The symptoms of anti-inflammatory response consist of swelling (tumor), heat (calor), pain (dolor), and redness (rubor) that inflammatory mediators such as prostaglandin, histamine, leukotriene, and serotonin, are being released (3,4).…”
Section: Introductionmentioning
confidence: 99%